MODEL PEMBELAJARAN GENDER DAN POLITIK: UPAYA PENINGKATAN POLITICAL AWARENESS SISWI SMU DI SURABAYA - Wigati, Wulan Retno (Global and Policy Journal of International Relations, 2015)
ABSTRACTYoung generation is one key factor for a country’s developments. Their participation in political process, especially in election process is important. Political participation is one of the key concept which implicitly connected to many political theory of democracy. As many political research already review about young generation’s political participation, this research also exploring the same thing in Surabaya female high school students. Using democratic perspective analysis this article trying to explain the level of their responsibility as a citizens.Keywords: Political Awareness, Gender, Election, Political ProcessDOI:https://doi.org/10.33005/jgp.v3i01.1966